Kekerasan dan Kekuasaan dalam Praksis Berbahasa: Memahami Kekerasan dalam Perspektif Galtung - Mudjia Rahardjo (el Harakah: Jurnal Budaya Islam, 2000)
As a social phenomenon, violence has attracted the interest of social scientists to further study, cultivate and explore its exploratory theorists. One of them is Johan Galtung. This paper explores Galtung's theory of violence in relation to language practice. According to Johan Galtung, violence occurs when humans are affected in such a way that actual physical and mental realizations are under their potential realization. Galtung will see something as violent if in the future the event can be overcome or prevented, but still left. As a symbolic reality, language can not be separated from the inner world of the wearer and the social setting that exists. These include social conflicts such as violence, murder, rape, looting, harassment, robbery, repression, and so on. Coinciding with the violent phenomenon that plagues this nation, modesty or ethical language is now experiencing erosion or extraordinary setbacks. To overcome this, ethics of language decency needs to be addressed in the context of language teaching in Indonesian cultural lands. Sebagai fenomena sosial, kekerasan telah menarik minat para ilmuwan sosial untuk lebih jauh mempelajari, menggeluti dan mencari  teoretis eksplanatorisnya. Salah satu di antaranya ialah Johan Galtung. Tulisan ini memaparan tentang teori kekerasan Galtung dalam hubunganya dengan praktik bahasa. Menurut Johan Galtung, kekerasan terjadi bila manusia dipengaruhi sedemikian rupa sehingga realisasi jasmani dan mental aktualnya berada di bawah realisasi potensialnya. Galtung akan melihat sesuatu sebagai kekerasan bila di masa mendatang peristiwa tersebut bisa diatasi atau dicegah, tetapi tetap dibiarkan. Sebagai realitas simbolik, bahasa tidak bisa lepas dari dunia batin pemakainya dan setting sosial yang ada. Termasuk di antaranya konflik-konflik sosial berupa kekerasan, pembunuhan, pemerkosaan, penjarahan, pelecehan, perampokan, penindasan, dan lain sebagainya. Berbarengan dengan fenomena kekerasan yang melanda bangsa ini, kesopanan atau etika berbahasa kini mengalami erosi atau kemunduran luar biasa. Untuk mengatasi itu, etika kesopanan berbahasa perlu disikapi dalam konteks pengajaran bahasa dalam lahan budaya Indonesia.